Computational Methods in Earthquake Engineering Volume 3 - Papadrakakis, Manolis; Plevris, Vagelis; Lagaros, Nikos D. (Computational Methods in Applied Sciences,, 2017)
This is the third book in a series on Computational Methods in Earthquake Engineering. The purpose of this volume is to bring together the scientific communities of Computational Mechanics and Structural Dynamics, offering a wide coverage of timely issues on contemporary Earthquake Engineering. This volume will facilitate the exchange of ideas in topics of mutual interest and can serve as a platform for establishing links between research groups with complementary activities. The computational aspects are emphasized in order to address difficult engineering problems of great social and economic importance. .